Development of Timedependent Surface Subsidence Over the Total Extractions Areas of the Potash Beds Stoped with Interchamber Yield Pillars - M. P. Nesterov (International Conference on Ground Control in Mining, 1998)
The method of predicting the time-dependent surface subsidence for gently-inclined potash deposits where total extraction using various sizes of yielding bamier pillars was discussed.